Selected Chapters from the Renin-Angiotensin System - Kibel, Aleksandar (IntechOpen, 2020)
Selected Chapters from the Renin-Angiotensin System aims to provide a comprehensive overview of the most important physiological and pathophysiological roles of the renin-angiotensin system (RAS). The complex and convoluted RAS has been investigated for many years and, through rigorous scientific research, many important and previously unknown components and functions of the RAS have come to light. These discoveries have been crucial in the understanding of this system and provide a basis for effective modulation of the system as part of therapeutic strategies for a number of widespread disorders. New studies are continuing to elucidate the RAS and the mechanisms associated with its functions. This book discusses relevant scientific knowledge about the RAS and intends to introduce the reader to cutting-edge research with an accentuation on the mechanisms at the functional/physiological and molecular/cellular levels.